FORM AND MODULATION OF METAPHOR TRANSLATION TO INDONESIAN OF VINGT-MILLES LIEUES SOUS LES MERS OF JULES VERNE - Yusi Asnidar; M. Syarif Sumantri; Ninuk Lustyantie (English Review: Journal of English Education, 2022)
This research aims to gain an in-depth understanding of the form and modulation of metaphor translation from French to Indonesian, its use in the communicative context of speech events. Furthermore, this study also looks at the relevance of the results of the translation of the form and modulation with mediation, plurilingual and pluricultural competences in the CEFR European standard language proficiency. The data sources used are the Novel Vingt-Milles Lieues Sous Les Mers by Jules Verne and its translated novel 20.000 Mil di bawah Laut by NH Dini. The data in this study is a metaphor in a broad sense. The most dominant form of metaphor translation used is reproduction. Next, there are substitutions and paraphrases. The combined form of reproduction+paraphrasing is found in the VLM metaphor translation. Equivalence of meaning is obtained by using explicit and implicit modulation, special and general meanings, and point of view. The context of speech events contributes to producing an equivalent and natural translation. The results of this translation indicate that translation activities are complex language activities and require precision and accuracy. Translating literary works requires cultural mastery and an advanced level of linguistic mastery. The competencies are described in the Petra Project terms of reference contained in the CEFR 2020 and CECRL 2018 terms of reference. Translating skills require guided practice acquired through a well-oriented education. The ability to understand metaphors and other cultures and be able to compare them by providing analogies in the local culture is a plurilingual and pluricultural competence.